DEVELOPING NURSING ENGLISH INSTRUCTIONAL MATERIALS BY USING SIMULATION TECHNIQUE TO INCREASE ENGLISH ORAL COMMUNICATION SKILL FOR NURSING UNDERGRADUATE STUDENTS - Tenny Murtiningsih; Ahmad Kailani (UMBanjarmasin, 2019)
Nursing English is one of the branches of English for Specific Purposes (ESP) that require the instructors to take into account specific students’ learning needs. This is a Research and Development aimed: (1) to know the problems which are faced by the nursing students in studying English, (2) to develop nursing English materials by using simulation technique. There were 58 nurse students of the sixth semester at a private university in Indonesia invited to participate in the study. The data were garnered through questionnaires. Interviews were also conducted with students, teachers and subject specialist teachers. To enrich the data focus group discussions were carried out. The findings indicated that students’ speaking skill increased even though this method seemed challenging to them. Subject specialist teachers were familiar with this teaching technique since in the nursing field almost all the subjects need a simulation. This research contributes to the TESOL methodology and future research may expand the findings from another perspective.